An interpretation of langmuir probe floating voltage signals in a cutting arc - Prevosto, Leandro (2009)
An experimental study of the electrostatic probe floating voltage signals in a cutting arc and its physical interpretation in terms of the arc plasma structure is reported. Sweeping electrostatic probes have been used to register the local floating potential and ion current at 3.5 mm from the nozzle exit in a 30-A arc generated by a high energy density cutting torch with a nozzle bore radius of 0.5 mm and an oxygen mass flow rate of 0.71 g · s-1. It is found that the floating potential signal presented a central hump with duration almost similar to that corresponding to the ion current signal but having also lateral wings with much larger duration. Capacitive coupling between the probe and the conducting body of the nozzle and arc as a source for the floating potential signal was discarded. It is assumed that the hump in these probe voltage signals results from the presence of an electrostatic field directed in the radial direction outward the arc axis that is caused by thermoelectric effects. The probe floating voltage signal is inverted using the generalized Ohm's law together with the Saha equation, thus obtaining the radial profiles of the temperature, particle densities, radial electric field, and potential of the plasma at the studied section of the arc. The resulting temperature and density profiles derived from our interpretation are in good agreement with the data published elsewhere in this kind of high-pressure arcs. There is not a straightforward connection between the measured hump amplitude in the floating signal (≈4 V) and the derived increase in the plasma potential between the arc edge and the arc center (≈10 V), due to the global zero current balance condition established by the finite size of the probe. It is shown, however, that the probe takes a floating potential value close to that corresponding to the plasma temperature at the probe center. © 2009 IEEE.